Analysis of User Needs in Designing Boarding House Accounting Information Systems Using the PIECES Framework - Syefira Ramadhani; Nurafni Eltivia; Nur Indah Riwajanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The boarding house X has 93 rooms with different facilities so that it is necessary to design a boarding house accounting information system to manage the business process. Before designing a system, it is necessary to analyze system needs as a framework that can help solve problems and categorize needs. The PIECES Framework method (Performance, Information and Data, Economics, Control and Security, Efficiency, Service) is useful for measuring the functional and non-functional needs of the accounting information system to be built. The results of this study show the overall average value of the importance of the six PIECES framework domains is 4.45 with the predicate VERY IMPORTANT. The data was obtained from 50 respondents who were residents of boarding house for daughter X. From this data, it can be concluded that it is necessary to design a boarding house accounting information system.